Analisis Manajemen Risiko dalam Mewujudkan Good Governance pada Aspek Keuangan di Pemerintah Kota Yogyakarta Menggunakan ISO 31000 - Salsabila Afra Safitri; Velysia Ratnawati Suparwito (CV Insan Kreasi Media, 2023)
Risk management is still not successfully implemented in all governments, including the Yogyakarta City Government, in the current government environment. The implementation of risk management in the Yogyakarta City Government is still ineffective compared to other regional governments. The objectives of the government can be achieved by performing risk management and implementing good governance, as discussed in PP Number 60 of 2008 and KMK Number 577/KMK.01/2019. The study will discuss how the Yogyakarta City Government uses risk management to good governance on financial aspects. This research uses a method of qualitative approach with a type of descriptive research analysis by conducting surveys at government agencies as a data analysis technique. According to the findings of this study, the implementation of risk management in the Yogyakarta City Government on the financial side is still less effective due to a number of problems, including a lack of clear outputs and outcomes, lack of adequate technological means, and the low level of discipline of officials in the Government of Yogyakarta. Keywords: risk management, government, good governance, finance.